1979
DOI: 10.1104/pp.63.2.367
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Theory Regarding Ambimobility of Xenobiotics with Special Reference to the Nematicide, Oxamyl

Abstract: A theory is presented to explain the phloem mobility of certain systemic xenobiotics that are not weak acids. It is shown that there is a theoretically optimum permeability that permits optimum circulation through the symplasm and apoplast (including the phloem and xylem) of Solanum tuberosum plants. The optimum permeability is large enough to permit substantial passive permeation into sieve cells in the source leaf and yet is small enough to permit phloem ransport with some retention. The optimum permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 6 publications
2
28
0
1
Order By: Relevance
“…Both factors would make the partitioning of these compounds into xylem sap less than optimal. It is known that the phloem delivery of a xenobiotic can be strongly influenced by many plant parameters (14,19). The differences in plant species, plant size, and experimental conditions between this study and the one by Briggs et al (3) may account for the small difference in the observed optimal log Kow values for TSCF.…”
Section: Calculation Of Transpirational Stream Concentration Factormentioning
confidence: 53%
See 1 more Smart Citation
“…Both factors would make the partitioning of these compounds into xylem sap less than optimal. It is known that the phloem delivery of a xenobiotic can be strongly influenced by many plant parameters (14,19). The differences in plant species, plant size, and experimental conditions between this study and the one by Briggs et al (3) may account for the small difference in the observed optimal log Kow values for TSCF.…”
Section: Calculation Of Transpirational Stream Concentration Factormentioning
confidence: 53%
“…It should be pointed out that the root pathway to xylem for the foliarly applied ambimobile xenobiotics (11,19) differs considerably from that of a soil applied xenobiotic. Following a foliar application, the phloem-mobile xenobiotic gets unloaded (symplastically, apoplastically, or both; [9]) from phloem in, or near, the stele ofthe root.…”
Section: Calculation Of Transpirational Stream Concentration Factormentioning
confidence: 99%
“…at least an order of magnitude less than the concentration in the phloem (0-5 to 1 mM). Further analysis can be made using the model of Tyree, Peterson and Edgington (1979) for the distribution within plants of 'plant protection' compounds of varying permeability values. Their analysis showed that continued cycling around aim tall plant of a foliarsupplied compound with a phloem transport velocity of 0-3 m h~^ was maximal w^hen 9-2 244 J-P was 3 X 10~* cm s~^.…”
Section: Immobility In the Phloemmentioning
confidence: 99%
“…Translocation through phloem is fundamental in the distribution of either natural or synthetic chemical compounds from mature leaves to growth regions in roots and stem (Vidal, 2002). There are mathematical models that allow efficient calculation of translocation rates of xenobiotics via phloem, according to membrane permeability, size of the phloem loading area, and other parameters (Tyree et al, 1979). After the herbicidal molecule is translocated via phloem and entered into an adjacent cell, neighboring cells also need to be achieved to allow for proper action of the herbicide.…”
Section: Herbicide Absorption and Translocationmentioning
confidence: 99%